Impact evaluation of SLM options to achieve land degradation neutrality in Tunisia: Junior officer monthly reports. - Fradi, Fajr (2017)
This report details mainly the author's professional activities performed with the ICARDA Centre in Amman (Jordan) for the period 1 December 2016 ' 30 July 2017, under the supervision of Dr. Quang Bao Le (Systems- and GIS-based Sustainable Land Management ' SLM, at ICARDA Amman), and Mr. Enrico Bonaiuti (Monitoring Evaluation and Learning ' MEL, ICARDA Amman).